Wednesday

April 1, 2015

April 1, 2015

Posted by **Ashley** on Thursday, November 4, 2010 at 2:03pm.

- logarithmic differentiation -
**Reiny**, Thursday, November 4, 2010 at 2:33pmfirst take ln of both sides

ln y = ln(x^-cosx)

ln y = -cosx lnx

now differentiate with respect to x

(dy/dx)/y = -cosx (1/x) + lnx (sinx)

dy/dx = y ( -(1/x)cosx + lnx(sinx))

= x^-cosx ( -(1/x)cosx + lnx(sinx))

**Answer this Question**

**Related Questions**

logarithmic differentiation - How do you find the logarithmic differentiation of...

Calculus - I need to find the derivative of the following problem via ...

logarithmic differentiation - How do you find the logarithmic differentiation of...

math - Use logarithmic differentiation to find the derivative of the function. y...

calculus - Use logarithmic differentiation to find dy/dx for y=(1+x)^(1/x).

Math - Use logarithmic differentiation to find the derivative of y: y=x^(e^x)

Calc - Use logarithmic differentiation to find dy/dx. y = sq. root [(x^2 - 1)/(x...

college - What do I do to Find dy/dx using logarithmic differentiation. y=(x^3)...

math - Use logarithmic differentiation to find the derivative of the function. y...

calc - Use logarithmic differentiation to find the derivative of the function. y...